Factors in Farmers' Decision-Making in the Implementation of the Good Agricultural Practices (GAP) System in Tilongkabila District - Ridwanto Ismail; Yanti Saleh; Ramlan Mustafa (Majapahit Journal of Islamic Finance and Management, 2026)
This study aims to analyze the effectiveness of corn farming management and to identify the factors influencing farmers’ decisions to adopt Good Agricultural Practices (GAP) in Tilongkabila District, Bone Bolango Regency. The research employed a descriptive quantitative approach using a survey method involving 30 corn farmers selected through purposive and snowball sampling techniques. Data were collected through observation, interviews, questionnaires, and documentation. The effectiveness of corn farming management was analyzed using a Likert scale and an effectiveness index, while the influence of social, economic, technological, and policy factors on farmers’ decisions to adopt GAP was examined using multiple linear regression analysis. The results indicate that corn farming management in Tilongkabila District falls into the effective category, with an average effectiveness score of 74.42%, covering aspects of planning, organizing, implementation, and supervision. Regression analysis shows that social, economic, technological, and policy factors simultaneously influence farmers’ decisions to adopt GAP; however, partially, only certain factors have a significant effect.